TEACHERS’ STRATEGIES IN ADDRESSING LOW LITERACY TO STRENGTHEN STUDENTS’ CHARACTER VALUES: A QUALITATIVE STUDY - Zuhri, Zuhri (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study aims to analyze teachers' strategies in overcoming low student literacy and their contribution to strengthening character values at Takhassus al-Qur'an Bonang Demak Junior High School. The phenomena of low reading interest, gaps in basic literacy skills, and the influence of socioeconomic factors and family parenting patterns are the main background of this study. The research uses a qualitative approach with a descriptive case study design. Data were collected through in-depth interviews, participatory observation, and documentation of 26 participants consisting of six teachers, one principal, one librarian, and eighteen students. Data analysis was conducted interactively through data reduction, categorization, thematic presentation, and verification to identify emerging patterns and meanings. The results of the study show that low literacy is not only influenced by limited facilities, but also by low intrinsic motivation, weak basic reading skills, family economic constraints, and changes in parenting patterns in the digital age. Teacher strategies such as learning variety, utilizing libraries as alternative learning spaces, book and gadget wakaf programs, and the application of peer teaching have been proven to contribute to increasing student engagement while strengthening character traits such as responsibility, empathy, polite communication, and critical thinking. This study confirms that literacy is a social practice that functions as an integrative medium between cognitive development and character building. The implication is that strengthening literacy requires an ecosystem approach that involves schools, families, and sustainable education policies. Further research is recommended to expand the context and use a longitudinal design to examine the long-term impact of character-based literacy strategies.